2020
DOI: 10.1186/s13023-020-01485-7
|View full text |Cite
|
Sign up to set email alerts
|

Variable phenotypes and outcomes associated with the MMACHC c.609G>A homologous mutation: long term follow-up in a large cohort of cases

Abstract: Background: Cobalamin C deficiency (cblC) caused by the MMACHC mutations is the most common type of the disorders of intracellular cobalamin metabolism. While the c.609G > A mutation is most frequent in Chinese cblC patients, its correlation with phenotype has not been delineated. Here we aim to investigate the factors affecting variable phenotypes and outcomes associated with the MMACHC c.609G > A homologous mutation in 149 Chinese cases to have implications for treatment and prevention. Methods: We assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 39 publications
2
24
3
Order By: Relevance
“…Outcomes of Chinese patients with homozygous c.609G > A MMACHC variant reported recently in several studies 15‐17 . In the largest study, neurodevelopmental outcomes were normal in 10 patients identified by NBS and treated from the age of 15 days 15 . The c.609G > A MMACHC variant was identified in five patients (either homozygous or compound heterozygous, one patient from the SX group and four patients from the NB group) in our study.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Outcomes of Chinese patients with homozygous c.609G > A MMACHC variant reported recently in several studies 15‐17 . In the largest study, neurodevelopmental outcomes were normal in 10 patients identified by NBS and treated from the age of 15 days 15 . The c.609G > A MMACHC variant was identified in five patients (either homozygous or compound heterozygous, one patient from the SX group and four patients from the NB group) in our study.…”
Section: Discussionsupporting
confidence: 51%
“…The pathogenic c.271dupA (p.Arg91Lysfs*14) variant is the most frequent variant in Caucasians, and is associated with an early disease onset (<1 year) 12 . Outcomes of Chinese patients with homozygous c.609G > A MMACHC variant reported recently in several studies 15‐17 . In the largest study, neurodevelopmental outcomes were normal in 10 patients identified by NBS and treated from the age of 15 days 15 .…”
Section: Discussionmentioning
confidence: 99%
“…c.609G>A was the most common variant found in Chinese patients with early onset cblC de ciency [21][22] . The c.658_660delAAG mutation was the third and the c.567dupT mutation was the fourth most common mutations.…”
Section: Discussionmentioning
confidence: 97%
“…Disease Markers an intrathecal chemotherapy-treated boy who suffered from leukemia [37]. And any transient elevation of Hcy may be related to the seizure risk [38,39]. Although it is hard to determine whether the elevated Hcy is the cause or the result of a seizure, we offered neurosurgeons a new insight into the prophylactic and off-label utility of antiepileptic drugs.…”
Section: Discussionmentioning
confidence: 99%